Dyspepsia Drug Use Pattern of Outpatients in a Public Health Center in Batununggal District Bandung - Linda Purnamawati Suherman; Pudjiastuti Kartidjo; Iis Rukmawati; Vina Septiani; Fazrin Azzura (Borneo Journal of Pharmacy, 2021)
Dyspepsia is a condition of pain in the epigastrium and a burning sensation that radiates to the chest. Dyspepsia occupies the 10th position in the 20 largest non-communicable diseases in a Public Health Center in Bandung. The heterogeneous symptoms and the absence of specific treatments can lead to irrational treatment. The research objective is to determine the pattern of drug use in patients with dyspepsia, including the right indication, the proper drug selection, the correct dose, and the proper interval of administration in a Public Health Center in Batununggal District Bandung. This study was an observational study using a cross-sectional study design that was descriptive in nature. The sampling technique employed the purposive sampling method retrospectively. The research was conducted on 104 patients diagnosed with dyspepsia with comorbidities and receiving drugs at an Outpatient Clinic in a Public Health Center in Batununggal District Bandung from January-March 2020. There were 38 male patients (36.538%) and 66 female patients (63.462%). The majority of patients were aged 56-65 years (28.846%). The most used drug class was antacids (60.448%), and the dosage form that was mostly used was tablets (40.299%). The most used single drug was antacids (51.923%), while the most used drug combination was antacids and omeprazole (23.077%). The accuracy of drug selection and the accuracy of indications were 100% correct, the accuracy of the dosage was 59.62% correct, the accuracy of the time interval for drug administration was 71% correct, and the accuracy of the duration of drug administration was 9.62% correct.